Biotechnology Production of Cell Biomass from the Endangered Kickxia elatine (L.) Dumort: Its Untargeted Metabolomic Analysis and Cytotoxic Potential Against Melanoma Cells - Anastasia Aliesa Hermosaningtyas; Ewa Totoń; Anna Budzianowska; Natalia Lisiak; Aleksandra Romaniuk-Drapała; Dariusz Kruszka; Monika Rewers; Małgorzata Kikowska (Biomedicines)
Background: Melanoma is a malignant tumor of melanocytes with an increasing incidence worldwide. Plant-based products are rich in bioactive compounds, offering low toxicity and accessible alternatives for melanoma treatment. A biotechnological approach to obtaining plant-derived produce ensures continuous and high-yield production of medicinally valuable biomass. Objectives: This study aimed to induce and optimize the growth of homogenous callus cultures of Kickxia elatine (L.) Dumort., consequently established a cell suspension culture with a high biomass growth rate, analyzed the phytochemical compositions, and assessed the cytotoxic activity against melanoma cells. Methods/Results: Callus cultures were induced under controlled in vitro conditions on Murashige and Skoog (MS) media supplemented with 2.0 mg L−1 Dicamba and 2.0 mg L−1 2,4-Dichlorophenoxyacetic acid. The selected callus lines exhibited a high growth index (351.71% ± 27.77) and showed a homogeneous morphology, beige colour, and had friable and watery characteristics. A combination of auxin and cytokinin was found to enhance biomass production significantly. Phytochemical investigations putatively annotated major compounds, including benzoic acid derivatives, phenolic glycosides, phenylpropanoic acids, hydroxycinnamic acid derivatives, and tyrosol derivatives. Methanolic extract (KE-Ex) and 40% methanolic fraction (KE-40Fr) were prepared and tested for cytotoxicity against human fibroblast (MRC-5) and melanoma (MeWo) cell lines using direct cell counting and MTT assay. The crude extract exhibited the strongest cytotoxicity effect on MeWo cells, with IC50 values of 125 ± 8 µg mL−1 after 48 h and 117 ± 7 µg mL−1 after 72 h of treatment. Conclusions: The extract demonstrated a time- and dose-dependent cytotoxic effect, making it a potential candidate for melanoma treatment.